2009
DOI: 10.1118/1.3213519
|View full text |Cite
|
Sign up to set email alerts
|

Dose prescription complexity versus tumor control probability in biologically conformal radiotherapy

Abstract: 5Purpose: The technical feasibility and potential benefits of voxel-based non-uniform dose prescriptions for biologically heterogeneous tumors have been widely demonstrated. In some cases, an "ideal" dose prescription has been generated by individualizing the dose to every voxel within the target, but often this voxel-based prescription has been 10 discretized into a small number of compartments. The number of dose levels utilized, and the methods used for prescribing doses and assigning tumor voxels to differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
15
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 50 publications
2
15
0
Order By: Relevance
“…They reported that the optimal dose distribution for eradication of a heterogeneous tumour is proportional to the spatial variation of the D 0 value within the tumour (D 0 is the dose required to reduce the number of surviving clonogens to 37% of its previous value) and the logarithm of the tumour cell density. Other studies have modelled the benefits of dose painting based on particular biological characteristics, such as tumour hypoxia [57e59] or clonogen density [60]. Ultimately, the true benefit for non-uniform dose distributions will only be fully appreciated once we have evidence from a clinical trial.…”
Section: Dose Paintingmentioning
confidence: 99%
“…They reported that the optimal dose distribution for eradication of a heterogeneous tumour is proportional to the spatial variation of the D 0 value within the tumour (D 0 is the dose required to reduce the number of surviving clonogens to 37% of its previous value) and the logarithm of the tumour cell density. Other studies have modelled the benefits of dose painting based on particular biological characteristics, such as tumour hypoxia [57e59] or clonogen density [60]. Ultimately, the true benefit for non-uniform dose distributions will only be fully appreciated once we have evidence from a clinical trial.…”
Section: Dose Paintingmentioning
confidence: 99%
“…A follow-up study by South et al [13] applied this theoretical framework to PET imaging using fluorodeoxyglucose 55 (FDG) as a tracer to ultimately describe a heterogeneous distribution reflecting radiosensitivity. We follow a similar framework as South et al [13] in this study to translate the PET image map to a desired heterogeneous dose distribution.…”
Section: Introductionmentioning
confidence: 99%
“…Our model uses a simplified treatment planning formulation that gives the treatment planner an adjustable parameter that can be used to adjust the conservatism of the resulting solution. The following theoretical framework, based on several models in the literature, [13] generates a heterogeneous desired dose distribution from PET SUV values and allows us to evaluate our models performance. This is not meant to represent a clinically validated function to map PET values to dose.…”
mentioning
confidence: 99%
See 2 more Smart Citations